Standards of the academic methodology in English language teaching - Ergashova , Shahrizoda (Science and Education, 2023)
The purpose of this article is to share the results of an investigation into how developmental didactics can help in the organization of sociology classes to promote the full development of students in the transition phase. It was carried out in higher education through a didactic formative intervention composed of adolescent students. This research led to the development of didactic principles aimed at guiding the organization of instruction aimed at the simultaneous development of teachers and students in the relationships they build in the classroom through pedagogical practices. These principles are more than prescriptive statements; they result from a theoretical elaboration of the teaching-learning development processes validated by practice in a specific concrete reality.